HAK AKSEPTOR KB ATAS PELAYANAN KONTRASEPSI DALAM PELAKSANAAN PROGRAM KELUARGA BERENCANA - JOKO NUR SARIONO, 0993311402 M (1998)
This research aims to study the relationship between act No. 10 of 1992 on Demographic Development and Development of Weltase families and Act No. 23 of 1992 on Health in an attemp to provide protection for fami ly Planning (FP) acceptors against contraception seviees on the fP program. Hence, in general this study discusses Law and Demographic Dynamic. Meanwhile, the specific abjective is to find out the legal subjects who are given the authority by the law to perform contraception services on the FP program, than to discribe the rights enjoyed by acceptors which are protected by the law from contraception services. Additionally, it specifically aims to study and find out the posible legal proceedings which can be taken by FP acceptors agains the services in case of malpractice or negligance causing injury on the part of acceptors. The research takes normative approach to the problem. Therefor,the types of data used are materials obtained from bibliographic study and inventory of statutory laws regarding Demographic and Family Planing. The legal materials are processed and analyzed by means of critical identification, then are selected and systematized based on their relevance to the matter at hand using deduction and induction eventuall y leading to the answer.